Identification and gene expression analysis of serine proteases and their homologs in the Asian corn borer Ostrinia furnacalis - Lei Yang; Xiaoli Xu; Wei wei; Xiaoyun Chen; Cheng Peng; Xiaofu Wang; Junfeng Xu (Scientific Reports, 2023)
Abstract Serine proteases (SPs) and their homologs (SPHs) are among the best-characterized gene families. They are involved in several physiological processes, including digestion, embryonic development and immunity. In the current study, a total of 177 SPs-related genes were characterized in the genome of Ostrinia furnacalis. The activation site of SPs/SPHs and enzyme specificity of SPs were identified, and the findings showed that most of the SPs analyzed possessed trypsin substrate specificity. Several SPs/SPHs with similar simple gene structures had tandem repeat-like distributions on the scaffold, indicated that gene expansion has occurred in this large family. Furthermore, we constructed 30 RNA sequencing libraries including four with developmental stage and four middle larval stage tissues to study the transcript levels of these genes. Differentially upregulated and downregulated genes were obtained via data analysis. More than one-quarter of the genes were specifically identified as highly expressed in the midgut in compared to the other three tissues evaluated. In the current study, the domain structure, gene location and phylogenetic relationship of genes in O. furnacalis were explored. Orthologous comparisons of SPs/SPHs between model insects and O. furnacalis indicated their possible functions. This information provides a basis for understanding the functional roles of this large family.